Environmental Design vs. Environmental Art Design: A Chinese Perspective - Yang, Yeqiu; Zhu, Dan (Journal of History Culture and Art Research, 2020)
Environmental (Art) Design is one of the most dynamic and studied design disciplines in China, derived and developed from Interior Decoration and Design. "Environmental Design" and "Environmental Art Design", two naming variations for the same discipline, coexist within the Chinese cultural context, in which many Chinese scholars developed their own comprehension of the nature of "Design". Therefore, these two names are often misused in Chinese academia and industry. The broad concept of "Environment" led to an ambiguity in the core, boundary, and scope of the discipline. Within this background, the discipline of Environmental (Art) Design is facing confusion and challenges. Similarly, today's design as a practice and research faces a dramatic change, focusing on "Ways of Thinking and Doing" instead of "Object". In this context, the mission and vision of the discipline of Environmental (Art) Design will opt for change accordingly. This article reviews a recent history of the discipline of Environmental (Art) Design, relevant key educational institutions, and opinions from prominent scholars. Furthermore, in the background of emerging design trends, new collective and constructive ideas and methods for Environment (Art) Design are also proposed. Finally, this paper alludes to the uniqueness and regionality of "Design Culture" in the Chinese context by studying the dispute over the name of China's Environmental (Art) Design.